Preverbal Production and Early Lexical Development in Children With Cochlear Implants: A Longitudinal Study Following Pre-implanted Children Until 12 Months After Cochlear Implant Activation - Majorano, Marinella; Brondino, Margherita; Morelli, Marika; Ferrari, Rachele; Lavelli, Manuela; Guerzoni, Letizia; Cuda, Domenico; Persici, Valentina (Frontiers in Psychology, 2020)
Studies have shown that children vary in the trajectories of their language development after cochlear implant (CI) activation. The aim of the present study is to assess the preverbal and lexical development of a group of 20 Italian-speaking children observed longitudinally before CI activation and at three, six and 12 months after CI surgery (mean age at the first session: 17.5 months; SD: 8.3; range: 10-35). The group of children with CIs (G-CI) was compared with two groups of normally-hearing (NH) children, one age-matched (G-NHA; mean age at the first session: 17.4 months; SD: 8.0; range: 10-34) and one language-matched (G-NHL; n = 20; mean age at the first session: 11.2 months; SD: 0.4; range: 11-12). The spontaneous interactions between children and their mothers during free-play were transcribed. Preverbal babbling production and first words were considered for each child. Data analysis showed significant differences in babbling and word production between groups, with a lower production of words in children with CIs compared to the G-NHA group and a higher production of babbling compared to the G-NHL children. Word production one year after activation was significantly lower for the children with CIs than for language-matched children only when maternal education was controlled for. Furthermore, latent class growth analysis showed that children with CIs belonged mainly to classes that exhibited a low level of initial production but also progressive increases over time. Babbling production had a statistically significant effect on lexical growth but not on class membership, and only for groups showing slower and constant increases. Results highlight the importance of preverbal vocal patterns for later lexical development and may support families and speech therapists in the early identification of risk and protective factors for language delay in children with CIs.